A Review of Meta-Model Designed for the Model-Based Testing Technique - Desamsetti, Harshith; Mandapuram, Mounika (Engineering International, 2017)
Recently, software engineering research has focused on IT system testing. Due to its practicality, academic and corporate research has presented various model-based testing methodologies. Model-based testing is a popular software technique that ensures system performance and evaluation. Automatic test case generation from requirements is intended to replace manual testing. Most of these approaches differ in critical areas like the specification paradigm and the model used to define requirements. Still, they share common principles, problems, and characteristics inherited from model-based testing. This paper proposes a meta-model that represents model-based testing principles and attributes to define the structure and entities of any new approach.